Kyai’s Psychological Resilience in the Perspective of Pesantren: Lesson from Indonesia - Rahmatullah, Azam Syukur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study focuses on exploring the experiences of the kyai who have founded a pesantren. Founding a pesantren can be interpreted as establishing, raising, and developing a pesantren. These activities, of course, lead to heavy psychological experiences. Although in the end, the kyai still did not step down from the struggle for the pesantren, whatever the challenges and obstacles they faced, their existence in developing resilience was increasingly strengthened. This study is field research using descriptive qualitative. The phenomenological approach is used in this study, which is an approach that pays more attention to the subjective experience of the individual. The setting of this study is the Tahfidzul Qur'an Al-Ma'ruf Pesantren in Kediri, East Java. The primary informant is Kyai Ahmad Fauzan Pujianto as the pesantren’s founder, developer, and caregiver. He has experienced firsthand the events during his time with the pesantren. The results of the study showed several findings, including the types of obstacles to the kyai, among others, receiving death threats, burned down residence, the access road to the house was closed, the recitation study was disbanded, receiving messages of witchcraft (santet), prejudice, and hate speech. The basic principles of the kyai’s resilience in facing these obstacles are as follows: it is mandatory to have the will and ability to annul all personal weaknesses, being free from mental blocking and toxic thoughts, self-function with an accuracy of view, and focusing on self-strength as a human being who is given the potential to develop. The kyai themselves have skills in developing their self-resilience, i.e., by learning ABCS, avoiding thinking traps, detecting icebergs, challenging beliefs, putting in perspective, calming, and focusing. Several factors affect the quality of the kyai’s resilience, including emotion regulation, impulse control, reaching out, a causal analysis. The benefits of this study are as a role model and as a form of self-preparation for (prospective) kyai to strengthen their mentality and self-resilience in facing any form of “tests and obstacles” when establishing, raising, and developing pesantren.